2006
DOI: 10.1002/anie.200600263
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Enantioselective, Pd–TangPhos‐Catalyzed Hydrogenation of N‐Tosylimines

Abstract: Although significant progress has been made in the catalytic asymmetric reduction of ketones and olefins over the last few decades, [1] the asymmetric reduction of imines remains a major challenge.[2] Enantioselective reductive amination with organocatalysts has recently been reported, [3] and a number of transition-metal-based catalysts, such as those containing Rh, [4] Ru, [5] Ti, [6] Zr, [6d] and Ir, [7] have been applied to the asymmetric hydrogenation of imines. However, this method has been less succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
52
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(53 citation statements)
references
References 55 publications
0
52
0
1
Order By: Relevance
“…[9][10][11][12] The reaction temperature and H 2 pressure had no dramatic impact on enantioselectivity of product 2a.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] The reaction temperature and H 2 pressure had no dramatic impact on enantioselectivity of product 2a.…”
Section: Introductionmentioning
confidence: 99%
“…In 1990, Oppolzer et al 1a first reported the asymmetric hydrogenation of cyclic N-sulfonylimines by using Ru catalysts with up to 99% ee after crystallization. Recently, Zhang et al 4 described a Pd-catalyzed asymmetric hydrogenation of a cyclic N-sulfonylimine with high enantioselectivity. However, for the above-reported catalytic systems, only one substrate derived from saccharin was reported.…”
Section: Introductionmentioning
confidence: 99%
“…The first hydrogenation of imino esters catalyzed by palladium complexes was described by Amii [10] and coworkers with up to 91% ee in 2001. Afterwards, highly enantioselectively Pd-catalyzed hydrogenations of N-diphenylphosphinyl ketimines and N-tosylimines were reported by us [11] and the Zhang [12] group, respectively [Scheme 1, Eq. (1)].…”
mentioning
confidence: 99%
“…MeOH and CH 2 Cl 2 led to very low reactivity (entries 13 and 14); TFE was found to be the optimal solvent, which is in accordance with the Pd-catalyzed hydrogenation of ketones and activated imines in the literature. [8][9][10][11][12][13][14][15][16] Subsequently, some commercially available bisphosphine ligands were examined under the above conditions. The results showed that axial chiral bidentate bisphosphine ligands L1-L4 and L6-L8 (Table 2, entries 1-4 and 6-8) gave full conversions with 58-75% ee.…”
mentioning
confidence: 99%
See 1 more Smart Citation